2018
DOI: 10.3390/ma11020321
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Nanomedicine Therapies to Counter the Rise of Methicillin-Resistant Staphylococcus aureus

Abstract: In a recent report, the World Health Organisation (WHO) classified antibiotic resistance as one of the greatest threats to global health, food security, and development. Methicillin-resistant Staphylococcus aureus (MRSA) remains at the core of this threat, with persistent and resilient strains detectable in up to 90% of S. aureus infections. Unfortunately, there is a lack of novel antibiotics reaching the clinic to address the significant morbidity and mortality that MRSA is responsible for. Recently, nanomedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 225 publications
(220 reference statements)
0
21
0
Order By: Relevance
“…Similarly, penicillin conjugated silver nanoparticles (PS) inhibits the growth of S. aureus with the lowest MIC value of 0.0125 mg/ml. Polymeric nanoparticles were also reported to display more effective antimicrobial activity against methicillin-resistant Staphylococcus aureus when compared with general antibiotics 8,26 . The lowest concentration to inhibit the growth of E. coli amongst the conjugates was observed when vancomycin was conjugated with silver nanoparticles and methanol extracts (VSM) with MIC value of 0.0125 mg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, penicillin conjugated silver nanoparticles (PS) inhibits the growth of S. aureus with the lowest MIC value of 0.0125 mg/ml. Polymeric nanoparticles were also reported to display more effective antimicrobial activity against methicillin-resistant Staphylococcus aureus when compared with general antibiotics 8,26 . The lowest concentration to inhibit the growth of E. coli amongst the conjugates was observed when vancomycin was conjugated with silver nanoparticles and methanol extracts (VSM) with MIC value of 0.0125 mg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilms are an exact mechanism of MRSA persistence and antibacterial resistance for which nanoscale approaches can offer a novel tool to fight infections. Metal nanoparticles are a broad field of attention to prevent MRSA infections development (Hibbitts & O'Leary, 2018). The common metals nanoparticles which have a robust antimicrobial feature, representing an ability to eliminate MRSA biofilms (Mocan et al, 2014;Vijayakumar et al, 2015;Ferreira et al, 2016;Alhadrami & Al-Hazmi, 2017;Aswathanarayan & Vittal, 2017;Guo et al, 2017;Hsueh et al, 2017;Mekkawy et al, 2017), as explained in (Table 3).…”
Section: Inorganic Metal Nanoparticlesmentioning
confidence: 99%
“…It has previously been identified that the attainment or loss of methicillin resistance impacts the biofilm phenotype formed, 20 with MSSA more likely to form biofilms consisting of icaADBC-encoded PIA (polysaccharide intercellular adhesion) or PNAG (Poly-N-acetylglucosamine) polysaccharide, 21,22 whilst the ica operon appears to be redundant for MRSA biofilm formation, which is instead dependent on surface proteins (such as the fibronectinbinding proteins) and extracellular DNA (eDNA) released from cells that have undergone autolysis. 22 Considering that the development of new drugs is a very long and costly process, 23,24 the repurposing of existing drugs is gaining traction. 25 On the other hand, strategies aimed to increase antimicrobial efficacy can help reduce the development of drug resistance, mainly by leading to a decrease in the drug concentration needed for the treatment and clearance of biofilm infections.…”
Section: Introductionmentioning
confidence: 99%